1994
DOI: 10.1007/bf03162551
|View full text |Cite
|
Sign up to set email alerts
|

Photo-CIDNP study of the splitting of the dinucleotidecis, syn-thymine dimer with reduced flavin as a sensitizer: Evidence for a thymine radical anion intermediate

Abstract: Abstraer. Photochemically induced dynamic nuclear pola¡ (photo-CIDNP) studies were performed on the splitting of c/s,syn 2'-deoxythymidylyl-(3'~5')-2'-deoxythymidine eyelobutane dimer (cs-dTp[]dT), using redueed flavin asa sensitizer. This system serves as a model for the light-indueed repair mechanism of thymine dimers in DNA by the enzyme photolyase. The CIDNP spectrum shows en¡ absorption of the two C6-H protons of the corresponding monomer dTpdT, which demonstrates that a thymine radical anion is involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…If all protons in site i are labeled at a given moment, we will find the equations giving us the concentration n i of chemical form S i . The equations for the concentrations are given by [2] and [3].…”
Section: Theory and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If all protons in site i are labeled at a given moment, we will find the equations giving us the concentration n i of chemical form S i . The equations for the concentrations are given by [2] and [3].…”
Section: Theory and Discussionmentioning
confidence: 99%
“…In particular, NMR is used to measure quantum yields for irreversible photochemical reactions (1) and, in addition, NMR branch of photochemically induced polarization of nuclei provides detection of short-lived radicals arising in flash photolysis of substances (2). Being a well-developed NMR tool, dynamic NMR spectroscopy (DNMR) is commonly used to obtain kinetic parameters of dark reversible chemical reactions in solutions (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three different experimental procedures for the definition of the effective tate constants and the quantum yield of responses ate considered.One of the numerous applications of nuclear magnetic resonance (NMR) spectroscopy is the study of photochemical reactions [1][2][3][4][5]. The use of NMR for investigating the quantum yields of irreversible photochemical reactions [1] is widely known.…”
mentioning
confidence: 99%
“…The use of NMR for investigating the quantum yields of irreversible photochemical reactions [1] is widely known. Besides, photochemicaUy induced dynamic polarization of nucleus allows one to examine [2,3] the short-lived radical alternate corpuscles which appear as a result of flash photolysis of substances. Recently it was shown that with the help of dynamic NMR (DNMR), the reversible photochemical processes [6][7][8] can be investigated in situ.…”
mentioning
confidence: 99%